2021
DOI: 10.1088/1742-6596/1969/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Convolutional Neural Network Architectures for Real Time COVID-19 Facial Mask Detection

Abstract: The late 2019 outbreak of Coronavirus Disease (COVID-19) had an indelible imprint on the humanity. The world is recovering from the outbreak but there is danger of a second wave of the outbreak. To get rid of the outbreak it is necessary to prevent the viral transmission and it is need of the hour to maintain social distancing and wear masks in public areas. The governments are providing strict guidelines to wear masks in public places. It is not manually feasible to check if people are wearing masks or not. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Even with insufficient training data, this strategy helps them perform well. This capability diminishes the likelihood of overfitting and enhances the effectiveness of processing extensive datasets [36] . The inherent characteristics of sequential CNN models motivate us to explore novel architectural designs.…”
Section: Methodsmentioning
confidence: 99%
“…Even with insufficient training data, this strategy helps them perform well. This capability diminishes the likelihood of overfitting and enhances the effectiveness of processing extensive datasets [36] . The inherent characteristics of sequential CNN models motivate us to explore novel architectural designs.…”
Section: Methodsmentioning
confidence: 99%
“…obileNetv2: everal works employ MobileNetv2 [144,[147][148][149][150][151] and similar detectors such as NASNetMobile [152]. In [153], an FMD technique that employs MobileNetv2 as a basis and performs transfer learning has been proposed and tested on SMFD.…”
Section: Lightweight Object Detectorsmentioning
confidence: 99%
“…In 2020, the National Multimedia Software Engineering Technology Research Center of Wuhan University has open sourced the RMFD (Real-World Masked Face Dataset) and the Institute of Information Technology of the Chinese Academy of Sciences has also open sourced the MAFA dataset. At the same time, Baidu has also open sourced a mask face monitoring model based on its Paddle framework [3] . Theoretical analysis found that most of the general target detection methods are suitable for face mask wearing detection tasks.…”
Section: Introductionmentioning
confidence: 99%